Tracking controller for uncertain wheel mobile robot: adaptive sliding mode control approach - Pham, Sen Huong Thi; Nguyen, Cuong Duc; Giap, Khanh Dang; Vu, Nga Thi-Thuy (Bulletin of Electrical Engineering and Informatics, 2023)
This paper presents a technique for developing a sliding mode controller (SMC) using the state model of wheel mobile robot (WMR). The control scheme which consists of a controller and a disturbances observer can eliminate system uncertainties, disturbances, and unknown wheel slips. To successfully implement the sliding mode tracking controller algorithm, first, the transformation is utilized to convert the kinematic and dynamic models to an equation of state, and then create a controller based on Lyapunov function. Subsequently, a disturbance observer is formulated based on a stable sliding surface, followed by the development of an adaptive sliding mode control (ASMC) for the system. Moreover, to verify the efficacy of the given strategy, simulations have been performed under the aforementioned disturbance conditions. Finally, the simulation results show that chattering effect is eliminated, and the impact of disturbances is also diminished, thus proving the viability and correctness of the proposed control algorithm.